Deoxyribonucleic acid methylation in the enhancer region of the CDKN2A/2B and CDKN2B-AS1 genes in blood vessels and cells in patients with carotid atherosclerosis - Yu. A. Koroleva; A. V. Markov; I. A. Goncharova; A. A. Sleptsov; N. P. Babushkina; N. R. Valiakhmetov; D. V. Sharysh; A. A. Zarubin; M. S. Kuznetsov; B. N. Kozlov; M. S. Nazarenko (Российский кардиологический журнал, 2020)
Aim. Comparative analysis of the deoxyribonucleic acid (DNA) methylation level in the enhancer region of the CDKN2A/2B and CDKN2B-AS1 genes (9p21.3 locus) in vessels with/without atherosclerotic lesions, as well as in leukocytes of patients with clinically relevant carotid artery (CA) atherosclerosis and healthy individuals.Material and methods. The group of patients with clinically relevant atherosclerosis included 22 individuals with severe stenosis (>80%) of CA. Samples of atherosclerotic plaques, presenting CA regions, and great saphenous veins, as well as peripheral blood samples (leukocytes) were obtained from patients. The control group consisted of 14 individuals with the mild CA stenosis (£24%) and without hemodynamically relevant changes; peripheral blood samples were obtained from each of them. DNA methylation level was assessed by targeted bisulfite sequencing of amplicons.Results. The tissue-specific methylation of 31 CpG-site in the CDKN2A/2B and CDKN2B-AS1 gene enhancer was established: the vascular tissues significantly differed from the peripheral blood leukocytes. At the same time, there was an increase in the methylation level of both certain CpG sites and whole analyzed CA region affected by atherosclerosis (48,6 [34,8; 62,0]%), compared with intact vessels, both arteries (25,2 [23,1; 41,60]%, p=0,0001) and veins (35,0 [31,6; 40,0]%, p=0,0039). Patients had lower methylation levels in all CpG sites in blood leukocytes compared to blood vessel samples (8,7 [6,1; 9,7]%; p<0,05). At the same time, the level of DNA methylation in the blood leukocytes of atherosclerotic patients does not differ from that in healthy individuals (9,3 [8,3; 13,6]%; p>0,8).Conclusion. In the present study, the relationship between an increase in the DNA methylation in the enhancer of the CDKN2A/2B and CDKN2B-AS1 genes in CA and their atherosclerotic lesions was revealed, as well as the tissue-specific DNA methylation between vessels and peripheral blood leukocytes.